Dynamical Elastic Moduli of the Ti-13Nb-13Zr biomaterial alloy by mechanical spectroscopy - Florêncio, Odila; Muñoz Chaves, Javier Andres; Silva Júnior, Paulo Sérgio da [UNESP]; Grandini, Carlos Roberto [UNESP]; Libardi, Walter; Schneider, Sandra Giacomin (ABM, ABC, ABPol, 2012)
Dynamical Elastic Moduli of the Ti-13Nb-13Zr biomaterial alloy were obtained using the mechanical spectroscopy technique. The sample with heat treatment at 1170K for 30 minutes and water quenched with subsequent aging treatment at 670 K for 3 hours (TNZ + WQ + 670 K/3 h), was characterized through decay of free oscillations of the sample in the flexural vibration mode. The spectra of anelastic relaxation (internal friction and frequency) in the temperature range from 300 K to 625 K not revealed the presence of relaxation process. As shown in the literature, the hcp structure usually does not exhibit any relaxation due to the symmetry of the sites in the crystalline lattice, but if there is some relaxation, this only occurs in special cases such as low concentration of zirconium or saturation of the stoichiometric ratio of oxygen for zirconium. Dynamical elastic modulus obtained for TNZ + WQ + 670 K/3 h alloy was 87 GPa at room temperature, which is higher than the value for Ti-13Nb-13Zr alloy (64 GPa) of the literature. This increment may be related to the change of the proportion of α and β phases. Besides that, the presence of precipitates in the alloy after aging treatment hardens the material and reduces its ductility.
Keywords: Ti-13Nb-13Zr; aging treatment; elastic modulus; anelastic relaxation